ENT300 - Fundamentals of Entrepreneurship Cookies' Tale / Shahirah Seruji... [et al.] - Seruji, Shahirah; Materang, Nur Alya Alisa; Ahmad Tarmizi, Aisya Ameera; Wan Abdullah, Syarifah Mordiah; Sa'fali, Nurul Farhana (2015)
A business plan is a formal statement of a set of business goals, the reasons why they are believed attainable, and the plan for reaching those goals. It may also contains background information about the organization or team attempting to reach this goals. A business plan is very important in an organization in order to have effective and efficient controls over the flow of the business organization. Business plan is also known as a working paper, business proposal project paper or prospectus.